(3GdMdGd hGdMQGes - (3CHh GdaVd QGTO GdhdjOjs
(3ChdgG (B:s
(3CeG HYO GYGffG Gddg Efg Ndb dg GdCQV djfJaY HgG s
(3BNQgG (B:s
(3hjef YdjfG HGdeZaQI hgh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI (B(170) s
(3JHUQI GdJQGLe(Bs
Keywords: (3CUhd Gdabgs